Moderating effect of parents’ anxiety about their children’s education between parent WeChat group use and online support among Chinese parents - Wang, Peng; Syed Zainudin, Sharifah Sofiah; Mohd Hasan, Nurul Ain; Liu, Lu (Redfame Publishing, 2024)
Previous studies have investigated the influence of social media as a digital resource for parental support. However, little research is available regarding parent WeChat groups and their impact in providing online parenting support. Given that parents in China frequently have specific anxiety around their children's education, this is an important research area. Thus, this study examines the moderating effect of Parents’ Anxiety about Their Children’s Education (PAE) in the relationship between parents WeChat group use and online support. Using a sample of primary school parents (N = 493), the study found a positive association between parents WeChat group use and online support. The results indicated that PAE moderated the association between parents WeChat group engagement and online support, but not for the relationship between parents WeChat group intensity and online support. This study contributes to expanding the literature in WeChat group use, online support and PAE in East Asian countries with similar social and cultural contexts.